التعليــم عن بعد في ظل جائحة كوفيد-19، بين حتمية الرقمنة وإنعدام المساواة في فرص التعليم تجارب دولية - غالم, الهام (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة إلى تحديد واقع التعليم عن بعد في ظل جائحة كوفيد-19، وذلك بتناولنا للاستجابات التعليمية التي قامت بها مختلف البلدان خلال هذه الازمة، وماإنجر عنها من اختلال في التعليم الدراسي أدى الى توظيف التكنولوجيا الرقمية بشكل متباين بين الدول. أدى في النهاية إلى ظهور إختلال في تحقيق مبدأ المساواة في التعليم بإعتباره من اهم ركائز أجندة التنمية المستدامة 2030. وخلصت الدراسة إلي ضرورة إستشراف أثر الازمة على التعليم للحد من الخسائر المستقبلية المحتملة، وتحسيس صناع القرار في قطاع التعليم بأهمية إعداد خطط مدروسة لضمان إستمرارية العملية التعليمية من خلال أنظمة تعليمية بديلة (منصات الكترونية، قنوات تلفزيونية واذاعية ...) ، وتحقيق إنتقال سلس إلى تبني التكنولوجيا الرقمية لخدمة جملة الأهداف المسطرة. وضرورة القيام بدراسات تقييمية للوقوف على العقبات وتحديد أبرز الاحتياجات وتداركها. EnterThe study aims to determine the reality of e-learning in light of the Corona pandemic, so that digital technology has been employed differently between countries. This led to the emergence of an imbalance in achieving the principle of equality in learning opportunities, as it is one of the most important pillars of the 2030 sustainable development agenda We concluded is necessary to anticipate the impact of the crisis on education, and to sensitize decisionmakers to the importance of preparing plans to ensure the continuity of the educational process, through alternative educational systems (electronic platforms,...), and to achieve a good transition to the adoption of hybrid education .And the need to conduct evaluation studies to identify and remedy obstacles
E-learning in light of Covıd -19 pandemic between the inevitability of digitization and inequality in educational opportunities, International experiences
مقال
Keywords: التعليم ; التعليم عن بعد ; جائحة كوفيد-19، ; مبدأ المساواة في التعليم; Education;E-learning; Covıd -19; the principle of equality in education.